Knitting technology a comprehensive handbook and practical guide - Spencer, David J. (Technomic ; Woodhead, 2001)
This latest edition of the definitive knitting technology textbook is an essential reference for all textiles students, textile engineers and technicians involved in knitted garment design and manufacture.